CONDITION OF THE TEETH AND JAWS IN THE CHILD POPULATION OF UKRAINE OF DIFFERENT EPOCHS - Kaskova, L.F.; Artem'ev, A.V.; Artem'eva, V.A.; Makovka, I.L. (World of Medicine and Biology, 2015)
Based on the study of skeletal remains of children population of Ukraine, who lived from the Copper Age to the Middle Ages and is attempting to determine the time of occurrence of orthodontic diseases. The main source of injury in these historic periods is traumatic injuries. Orthodontic diseases not found. Epidemiological analysis of caries process and old based on the odontology collections of inhabitants of the Cooper Age to the late Middle Ages from Ukrain. Differens oll diseases of skeletal, jaws and teeth people hu live in old time. The first manifestations of abnormalities in children, as part of the reduction process, can be traced to the Middle Ages. This is due to food intake. Food were more careful thermal processing and became softer. Traumatic injuries of teeth in the Middle Ages, for example, more than twice than in the preceding period. All manifestations observed anomalies described by modern medical science; it is presented of the Middle Ages. The number of these variations is much smaller than that of the child population today accommodated. The obtained results lead to the conclusion about the need for additional measures to strengthen odontology and further study of dental diseases in different historical times in different territories.